User interface (UI) on self-service kiosks’ machine in fast-food industry in Nueva Ecija, Philippines: Its’ correlation towards customers’ experiences - Jesus, Fhrizz S. De; Nocum, Carl Louie; Punzal, Citadel; Villanueva, Filwyn (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze the impact of human-computer interaction (User Interface) on self-service kiosks in the fast food industry in Nueva Ecija, Philippines, and how it affects customer experiences. The study aimed to outline the demographic characteristics such as age, gender, and education level, as well as how often individuals visited fast food restaurants. Additionally, it evaluated participants' opinions on the user interface of self-service kiosks in fast food establishments, focusing on ease of use, satisfaction, and intention to continue using them. Based on the findings of the research, most of the participants aged 21 to 35 utilized self-service kiosks at fast-food establishments, with 66.9% being female. Most of the participants, accounting for 31.5%, are college undergraduates who visit the fast food restaurant on a weekly basis. Utilizing a self-service kiosk at a fast food establishment is simple and convenient, streamlining the service process. Patrons at the fast-food establishment had a positive experience utilizing the self-service kiosk and plan to keep using it to streamline their ordering process. When faced with the issue, 41.04% of respondents experienced technical and mechanical problems that disrupted their ordering process or timing. Based on the findings, recommendations have been crafted, including a development plan created by the researcher to enhance the storage operation.